Video processing and computational video international seminar, Dagstuhl Castle, Germany, October 10-15, 2010. Revised papers - Cremers, Daniel; Magnor, Marcus; Oswald, Martin R.; Zelnik-Manor, Lihi (Lecture Notes in Computer Science, 2011)
With the swift development of video imaging technology and the drastic improvements in CPU speed and memory, both video processing and computational video are becoming more and more popular. Similar to the digital revolution in photography of fifteen years ago, today digital methods are revolutionizing the way television and movies are being made. With the advent of professional digital movie cameras, digital projector technology for movie theaters, and 3D movies, the movie and television production pipeline is turning all-digital, opening up numerous new opportunities for the way dynamic scenes are acquired, video footage can be edited, and visual media may be experienced. This state-of-the-art survey provides a compilation of selected articles resulting from a workshop on Video Processing and Computational Video, held at Dagstuhl Castle, Germany, in October 2010. The seminar brought together junior and senior researchers from computer vision, computer graphics, and image communication, both from academia and industry, to address the challenges in computational video. During this workshop, 43 researchers from all over the world discussed the state of the art, contemporary challenges, and future research in imaging, processing, analyzing, modeling, and rendering of real-world, dynamic scenes. The 8 thoroughly revised papers presented were carefully reviewed and selected from more than 30 lectures given at the seminar. The articles give a good overview of the field of computational video and video processing with a special focus on computational photography, video-based rendering, and 3D video.